PERAN TOKOH AGAMA DALAM PENYUSUNAN PERATURAN DESA PERSPEKTIF SIYASAH SYARI’IYYAH - Rizkhyawan, A. Ryan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2023)
Religious leaders have a strategic role as agents of social change and community development through ideas, written works, or direct roles. For this reason, this study is intended to find out how the role of religious shops in the preparation of village regulations using the type of field qualitative research with a normative juridical approach and a normative theological approach (syar’i). The results of the study show that the formation of village regulations in Saotengnga Village was carried out through deliberation and an open mechanism that required the active role of the community, including the involvement of religious leaders in providing input and suggestions on the draft village regulations and sitting together the need for regulations in the village that support the development of rural areas. Meanwhile, the role of religious leaders in drafting village regulations from the Siyasah Syari’iyyah perspective is personal responsibility in carrying out da’wah to guide the people, implementing amar ma’ruf nahi mungkar, setting good examples and examples to the community, providing explanations to the community on various kinds of Islamic teachings originating from the Al-Qur’an and Sunnah, providing solutions to the problems of the people, forming a moral and virtuous orientation of society’s life and being mercy to all nature.